(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Omar Khayyam’s belief in understanding the world, his emphasis on the role of reason in this process, and his position as a follower of a particular philosophical school are evident. Similar thoughts about Khayyam were also observed, analyzed, and evaluated in the works of Shakespeare, offering a new approach to recognizing the poet’s trends in thinking.